2015
DOI: 10.1111/acem.12698
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Computed Tomography Utilization and 30-day Revisitation in Emergency Department Patients Presenting With Abdominal Pain

Abstract: Objectives: The objective was to explore which patient characteristics are associated with repeat emergency department (ED) visitation within 30 days of ED discharge for patients presenting with abdominal pain. Methods: A retrospective, observational study was conducted at a single, academic, urban ED with over 85,000 annual visits. A consecutive sample of adult patients with a chief complaint of abdominal pain from January 2010 through December 2010 who were discharged following ED evaluation were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
3
16
0
1
Order By: Relevance
“…The news media, policymakers, patients, and healthcare providers have called CT utilization into question 23 , 36 , 37 because diagnostic imaging is considered one of the key drivers of increasing healthcare cost in the U.S. 38 One study reported that use of abdominal CT was associated with decreased revisits, 39 but other studies have suggested that outcomes are not necessarily improved with more imaging. 40 – 44 The prevalence of over-testing, over-diagnosing, and over-treating has been criticized in modern medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The news media, policymakers, patients, and healthcare providers have called CT utilization into question 23 , 36 , 37 because diagnostic imaging is considered one of the key drivers of increasing healthcare cost in the U.S. 38 One study reported that use of abdominal CT was associated with decreased revisits, 39 but other studies have suggested that outcomes are not necessarily improved with more imaging. 40 – 44 The prevalence of over-testing, over-diagnosing, and over-treating has been criticized in modern medicine.…”
Section: Discussionmentioning
confidence: 99%
“…There are also measurable benefits of advanced imaging. For example, utilizing CTs for some ED conditions is also associated with lower ED returns, and CT use has been associated with lower negative appendectomy rates . Measuring and rewarding diagnostic efficiency might incentivize more rational test ordering, but defining “diagnostic efficiency” is an unmet challenge.…”
Section: Challenges To Reducing Testing In Emmentioning
confidence: 99%
“…Despite substantial improvement in the diagnostic approach to AAP, mainly attributable to the extensive use of imaging techniques [especially computed tomography (CT)], many diagnostic pitfalls remain, which can be associated with a substantial number of misdiagnoses and/or avoidable surgery (6)(7)(8). The differential diagnosis of AAP in the adult population is rather broad, including appendicitis, peptic ulcer, urinary stones, inflammatory bowel disease, hepatobiliary diseases (e.g., biliary colic, cholecystitis, and pancreatitis), referred pain due to pneumonia as well as several other "mimics" of extra-abdominal origin (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%